TEACHER’S PREPARATION OF LESSON PLANS IN ENGLISH FOR OCCUPATIONAL PURPOSES (EOP) THROUGH GOOGLE CLASSROOM - Detiani, N. K. (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
In the application of online learning, there are several problems. One of the problems that are often found is the problem of learning facilities. Students have inadequate to carry out online learning facilities so that the impact on online learning does not run optimally. This study aims to measure EOP teachers' ability to prepare EOP students' lesson plans through Google Classroom in Vocational High Schools (SMK) and identify teacher problems and problems faced by students in EOP learning through Google Classroom. The type of research ii is qualitative. The research was conducted using an embedded mix-method design. The participants of this study were an English teacher of tenth-grade students and 76 students. The methods used to collect data are observation, interviews, and questionnaires. The technique used to analyze the data is qualitative and quantitative statistical analysis. The results of this study indicate that teachers are lacking and have problems in three aspects. The three aspects are the relevance of learning methods, evaluation and learning indicators' relevance, and instruments and evaluations' relevance. In addition, EOP students found problems in 6 aspects of EOP learning through Google Classrooms. This research implies that EOP learning through Google Classroom can be applied by teachers in online learning.